Calculation of the contact area between snow grains and ski base. (November 2021) - Mössner, Martin; Hasler, Michael; Nachbauer, Werner
Abstract: Gliding friction depends on the contact area between ski and snow. Therefore, we computed the contact area of a single grain with the ski base by solving the static contact problem. The calculations were done at randomly selected positions on two ski bases, various snow grain radii, and various loadings. The relative single grain contact area with the ski base was 0.03–6.0% of the snow grain's cross section. Contact area and pressure increased with decreasing snow grain radius and increasing load. The contact pressure exceeds the strength of ice, presumably causing fracture of parts of snow grains. Resulting debris may partly remain in the interface between ski and snow and thus reduce friction. Highlights: Modeling and calculation of the contact area in the static contact between single snow grains and ski bases was accomplished. Only small fractions of snow grains contact with the ski base. Contact area and pressure vary strongly with sub-structures in the visible structure of the ski base. In small parts of the contact area, the contact pressure is above the strength of ice causing fracture of ice.